Cureghem: from demolition to revitalisation - Muriel Sacco (Brussels Studies, 2010)
This article focuses on the changes initiated by the new public policies for the urban revitalisation of “vulnerable” neighbourhoods in Brussels. The analysis of Neighbour-hood Contracts in Cureghem allows a better understanding of how the pre-existing context shapes this institutional innovation and of how a new public policy contributes to transforming political action. With the Neighbourhood Contracts, the municipal authorities of Anderlecht have gone from a project to demolish Cureghem to a project to revitalise it. However, this change was gradual. At first, the implementation of this mechanism in Cureghem revealed considerable inertia on behalf of the municipality due to its political and administrative culture and its lack of involvement in this new project. The objectives of this regional policy were achieved with the partial reconstruction of the local political landscape and the learning opportunities provided by the mechanism. The case of Cureghem thus demonstrates the role of local stakeholders in the creation of a public policy.